Mobile applications: some possibilities for teaching Chemistry (Research, Society and Development, 2020)
This study presents a survey of applications related to chemistry for mobile devices with Android operating system, available on the Google Play Store, and analysis of their characteristics and potential as tools for the teaching-learning process in the context of mobile learning. For this, the applications resulting from our search were categorized and the apps with the highest number of downloads and the best evaluation scores within each category were analyzed. Based on the analysis carried out, the study describes the main characteristics of 24 applications and, according to them, establishes possibilities for using these apps in the teaching-learning process in view of the needs and objectives of students and teachers and the skills established in the National Common Curricular Base for high school in the area of natural sciences and their technologies.